Asynchronous appearance of newly synthesized histone H1 subfractions in HeLa chromatin (The Rockefeller University Press, 1981)
Incorporation of radioactive alanine into chromatin-bound subfractions of H1 histone was studied in HeLa cells synchronized by the double thymidine block technique. The subfractions were resolved into three chromatographic peaks by Biorex-70. In the period 5-7 h after release from the thymidine block, peaks I and III showed twice as much incorporation as they did in the period 1-3 h after release, whereas peak II showed three times the incorporation at 5-7 h that it did at 1- 3 h. Thus, the H1-histone subfraction in peak II appears in chromatin somewhat later in S phase than do the subfractions in Peaks I and III.